2010
DOI: 10.1002/jbmr.202
|View full text |Cite
|
Sign up to set email alerts
|

Astacin proteases cleave dentin sialophosphoprotein (Dspp) to generate dentin phosphoprotein (Dpp)

Abstract: Dentin sialophosphoprotein (Dspp) is critical for proper dentin biomineralization because genetic defects in DSPP cause dentin dysplasia type II and dentinogenesis imperfecta types II and III. Dspp is processed by proteases into smaller subunits; the initial cleavage releases dentin phosphoprotein (Dpp). We incubated fluorescence resonance energy transfer (FRET) peptides containing the amino acid context of the Dpp cleavage site (YEFDGKSMQGDDPN, designated Dspp-FRET) or a mutant version of that context (YEFDGK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 47 publications
2
70
0
Order By: Relevance
“…The sequential extraction of proteins from dentin powder (40 g) of molars was carried out by the use of our previous demineralization method with 0.17 HCl and 0.95% formic acid (Tsuchiya et al, 2011). The supernatant obtained from 0.5 M acetic acid/2 M NaCl solution (AN extract) was used to isolate DSP and DPP.…”
Section: Sequential Extraction Of Proteins From Dentin Powder Of Molarsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequential extraction of proteins from dentin powder (40 g) of molars was carried out by the use of our previous demineralization method with 0.17 HCl and 0.95% formic acid (Tsuchiya et al, 2011). The supernatant obtained from 0.5 M acetic acid/2 M NaCl solution (AN extract) was used to isolate DSP and DPP.…”
Section: Sequential Extraction Of Proteins From Dentin Powder Of Molarsmentioning
confidence: 99%
“…The AN extract (150 mg) was fractionated by IE chromatography in a Q-Sepharose Fast Flow column (1.6 x 20 cm; GE Healthcare UK Ltd, Little Chalfont, UK) by our previous method (Tsuchiya et al, 2011). The DPP and DSP in the third (ANQ3) and high-molecular-weight (HMW)-DSP in the fourth (ANQ4) fractions were dialyzed against water, lyophilized, and characterized by SDS-PAGE and ALP-HPDL system with or without the TGF-β specific inhibitor, SB431542.…”
Section: Isolation Of Dpp and Dsp From Molar Dentinmentioning
confidence: 99%
“…It has been suggested that the proteolytic processing of DSPP to DPP, DSP and DGP is the activating stage in the mechanism of DSPP function (Zhang et al 2001. The cleavage of DPP from DSPP is catalysed by a group of zinc metallopeptidases that includes BMP1, and it is this fragment of DSPP that contains the ASARM peptide (Tsuchiya et al 2011). Various studies have shown DPP to be important in the formation and growth of HA as it has a strong affinity to Ca 2C when bound to collagen fibrils (Boskey et al 1990, Saito et al 1997, He et al 2005.…”
Section: Dentin Sialophosphoproteinmentioning
confidence: 99%
“…Mutation of certain conserved residues outside of the P 4 -P 4 Ј region also had significant effects on processing. We also found that the effects of mutations of DSP-PP 240 on cleavage by purified recombinant human BMP1, a candidate physiological processing enzyme (5,6,15), paralleled the effects on cleavage by the Sf9 cell processing activity (13) explained by the high degree of conservation between the substrate-binding clefts of the candidate Sf9 cell and human processing enzymes.…”
mentioning
confidence: 63%
“…Additional studies devoted to identifying the exact DSP-PP cleavage site by Steiglitz et al (20), von Marschall and Fisher (6), and Yamakoshi and co-workers (15,21) have been summarized by Ritchie et al (13).…”
mentioning
confidence: 99%